Heat treatment of colostrum increases immunoglobulin absorption in Holstein heifer calves - Salazar-Acosta, Ericka; Elizondo-Salazar, Jorge Alberto (Agronomía Mesoamericana, 2019)
Introduction. The best line of defense against invading pathogens in the newborn dairy calf is the immunoglobulins from colostrum that are absorbed in the small intestine. Objective. The objective of this work was to determine the efficiency of absorption of inmunoglobulins G (IgG) in Holstein heifer calves by supplying low and good quality heat-treated calostrum. Materials and methods. The study was carried out from August 2016 to August 2017 in a commercial dairy farm in Las Nubes de Coronado, San José, Costa Rica. First milking colostrum was collected from fifty Holstein cows, placed into plastic containers and separated into two categories (low<50 and high≥50 g of immunoglobulin/l). Colostrum within each category was pooled and mixed to create two unique uniform batches, half of each batch (35 l) was transferred into containers properly identified and frozen until required for feeding (colostrum without heat treatment). The remaining half of each colostrum half was heated to 60 °C and maintained for 30 min in a commercial pasteurizer. The different colostra were analyzed for total coliforms, fecal coliforms and E. coli, fat, crude protein, lactose, total solids and total IgG concentration. Blood samples were obtained from 36 calves and were analyzed for total serum protein, IgG and ºBrix. Results. Heat treatment significantly reduced bacterial population and maintained IgG concentration. Heat treatment significantly increased (P<0.001) total serum IgG concentration regardless of colostrum quality. IgG concentration increased from 15.9 to 23.8 and 3.9 to 8.1 % for the high and low quality group, respectively. Heat treatment also increased apparent efficiency of absorption; there was an increase from 16.0 to 31.1% for the group of calves consuming high quality colostrum and from 12.7 to 32.7% for the group consuming low quality colostrum. Conclusion. Feeding heat-treated colostrum to new born Holstein heifer calves significantly increased apparent efficiency of absorption, therefore, IgG concentration in animals’ blood serum.